Strength properties of hydrated gypsum powder - Fedelia, Anak Fedrick Ali (Universiti Malaysia Sarawak (UNIMAS), 2017)
Gypsum is a sulfate mineral composed of calcium sulfate dehydrate [CaSO4·2H2O]. Natural gypsum usually taken from mining, it will be grounding and crushing to produce gypsum powder. Gypsum powder is widely used as fertilizer in agriculture industry and in construction it is widely used as a plaster, blackboard chalk and wallboard. Furthermore, gypsum is moderately soluble in water (2.0–2.5 g/l at 25 °C). The production of gypsum, when being heated it can formed or convert to calcium sulfate hemihydrate which often known as plaster and further it can convert to anhydrous calcium sulfate which has a high solubility in saline solutions. Recently, gypsum powder is being produced through synthetic method called Flue-Gas Desulfurization. Natural gypsum and FGD gypsum share the same composition even though FGD gypsum is a synthetic production. FGD gypsum is environment friendly which its purity exceeding 96% unlike the natural gypsum that has a purity range 70%-90%. From this undertaking, gypsum powder was used to find and investigate its strength properties. In dam construction, mostly the land area where the construction takes place containing gypsum and as has been mentioned, gypsum is a soft mineral that are very soluble when contact with water. These characteristics of gypsum will cause damage to the dam and it will affect many things surround it. Therefore, from this undertaking, gypsum powder was used to find and investigate its strength properties. As the work of the gypsum mechanical is still vague, further investigation on gypsum was done and the solution to the problem can be solved.